GAYA BAHASA HIPERBOLA DALAM NOVEL PULANG KARYA TERE LIYE - Etami, Gemmi; Hamsa, Akmal; Baharman, Baharman (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2025)
This research aims to: describe the characteristics of hyperbolic language style and describe the function of using hyperbolic language style in the novel "Pulang" by Tere Liye. This type of research is qualitative. The instruments used in this research are human instruments or the researchers themselves. The data collection technique in this research uses library study techniques. The data analysis technique used in this research is the Miles and Huberman model which includes data reduction, data display and conclusion. The results of this research show that the novel "Pulang" by Tere Liye uses four characteristics of hyperbolic language style, namely unreasonableness such as describing the character of a situation that is far beyond reasonable possibilities, exaggeration such as mentioning passionate feelings or unbearable suffering. , dramatic such as creating a dramatization of the emotional power of a conflict or climactic moment, and has the ability to influence the reader or listener to feel a certain intensity and accept a stronger idea. Furthermore, the function of hyperbolic language style in the novel "Pulang" by Tere Liye is to provide a dramatic effect to increase tension and create deep feelings, to beautify sentences to create impressive images, to make the story more lively and colorful, to emphasize emotions to present deep emotional nuances, and increase the attraction to the reader to create an amazing picture, so that the novel is more interesting and beautiful.